Principles of cross‐network communication in human resting state fMRI. Issue 1 (22nd January 2018) - Mitra, Anish; Raichle, Marcus E.
Abstract : Directed signaling among and within the large‐scale networks of the human brain is functionally critical. Recent advances in our understanding of spontaneous fluctuations of the fMRI BOLD signal have provided strategies to study the spatial‐temporal properties of directed signaling at infra‐slow frequencies. Herein we explore the relationship between two canonical systems of the human brain, the default mode network (DMN) and the dorsal attention network (DAN) whose anti‐correlated relationship is well known but poorly understood. We find that within the DMN, activity moves from retrosplenial to prefrontal cortex whereas in the DAN activity moves from the frontal eye fields to the parietal cortex. Bi‐directional communication between the two networks occurs via their earliest elements (i.e., from the retrosplenial cortex of the DMN to the frontal eye fields of the DAN). This framework for network communication appears to generalize across all networks providing an expanded basis for understanding human brain function.